Equivalent simulation method for total pressure distortion of ship inlet - Wang, Zhong-Yi; He, Chenxin; Wu, Yue; Qu, Yong-Lei (Frontiers in Energy Research, 2024)
According to the use of marine gas turbines, inlet distortion is caused by the bending of the compressor inlet port. The total pressure distortion is the external stability reduction factor that has the greatest impact on the engine’s aerodynamic stability. This research designs a pressure distortion simulation device, which achieves the goal of providing the target distortion flow field for marine compressors by inserting plugboards of different heights and shapes into the inlet duct. The variation pattern of the entire flow field after inserting different parameter plugboards is obtained through distortion experiments and numerical simulations. Summarizes a prediction formula for total pressure distortion under different working conditions, with a verified error of less than 1.5%. In addition, the straight plugboard is changed to arc plugboard or concave and convex plugboard, the total pressure distortion distribution pattern can be changed while the range of the circumferential low-pressure zone remains unchanged. The distortion index of the distortion simulator designed by this research institute can be adjusted within the range of 0.5%–5%, while providing various distortion pattern. The distortion simulator meets the requirements of the comprehensive distortion index needed for the relevant distortion test of the marine engine and provides assistance for ship engine design and optimization.